2013
DOI: 10.1017/s0007485313000576
|View full text |Cite
|
Sign up to set email alerts
|

Fitness costs associated with field-evolved resistance to chlorantraniliprole inPlutella xylostella(Lepidoptera: Plutellidae)

Abstract: Plutella xylostella (L.) is the most important pest of Brassicaceae worldwide, with a recent estimate of US$ 4-5 billion expenditure for the control of this insect. A case of very high resistance of this pest to chlorantraniliprole was recently associated with reduced efficacy in a Brazilian field of Brassica spp. Although diamide resistance has been characterized, the fitness of insects due to such resistance has yet to be examined. Therefore, in this study, biological parameters were assessed in both suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
2
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 45 publications
(55 reference statements)
6
84
2
11
Order By: Relevance
“…Similar data has also been collected for susceptible field strains from Brazil (Ribeiro et al, 2014, da Silva et al, 2012) and Japan (Steinbach et al, 2015). …”
Section: Baseline Susceptibility Monitoring For Diamide Insecticidessupporting
confidence: 58%
“…Similar data has also been collected for susceptible field strains from Brazil (Ribeiro et al, 2014, da Silva et al, 2012) and Japan (Steinbach et al, 2015). …”
Section: Baseline Susceptibility Monitoring For Diamide Insecticidessupporting
confidence: 58%
“…A second key question concerning the Italian populations is on the resistance mechanisms in the particular environment. Studies in diamide resistant P. xylostella have shown that reversal of resistance may occur in absence of selection pressure (Wang et al 2013;Ribeiro et al 2014). On the other hand, other P. xylostella strains have shown long term stability suggesting absence of fitness cost (Steinbach et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, intensive and repetitive use of the diamides have led to the rapid development of resistance in both P. xylostella and S. exigua 781014.…”
Section: Discussionmentioning
confidence: 99%